ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT. UNILEVER INDONESIA, TBK - Guntur Rahmat Putra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the financial performance of PT. Unilever Indonesia, Tbk during the period 2016-2020. The object of this research is PT. Unilever Indonesia, Tbk and the research population are Financial Statements for the 2016-2020 period which includes balance reports, income statements, and others. The type of research used is quantitative method. Data collection through documentation. The data of this research were obtained from www.unilever.com . The data analysis technique used is Economic Value Added (EVA) analysis obtained from the difference in the NOPAT value minus the value of Capital Charges. The results showed the financial performance of PT. Unilever Indonesia, Tbk seen from the year of the study the average score was positive (EVA < 0), but there were still fluctuations. The period that experienced a negative value (EVA > 0) was only in 2019. This was because the value of WACC and Capital Charges decreased from the previous year. Despite experiencing fluctuations, PT. Unilever Indonesia, Tbk in 2016-2020 can be said to be able to provide added economic value for shareholders. Keywords: Financial Performance, Economic Value Added (EVA)